2021
DOI: 10.1002/cam4.4130
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of axitinib versus sunitinib as first‐line therapy to patients with metastatic renal cell carcinoma in the immune‐oncology era

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In our clinical practice, vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKIs) have become the standard of care for mRCC [ 31 ]. Sunitinib, a broad-spectrum inhibitor of receptor tyrosine kinases, has been widely used as the standard of treatment for first-line therapy of advanced ccRCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical practice, vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKIs) have become the standard of care for mRCC [ 31 ]. Sunitinib, a broad-spectrum inhibitor of receptor tyrosine kinases, has been widely used as the standard of treatment for first-line therapy of advanced ccRCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic perspective, it is observed that some patients with kidney cancer develop different resistance to the most widely used drugs, such as sunitinib and axitinib, suggesting that different correlations between pyroptosis and tumor-immune microenvironments occur [ 109 , 123 , 124 ]. Moreover, different tumoral microenvironment-infiltrating cell populations are already considered an unfavorable prognostic factor for ccRCC.…”
Section: Pyroptosis In Kidney Cancermentioning
confidence: 99%
“… 7 , 8 , 9 , 10 , 11 , 12 Treatment with ICIs in combination or ICIs plus TKIs is considered the standard of care for patients with metastatic RCC. 13 , 14 , 15 , 16 , 17 , 18 Furthermore, immune‐related AEs are closely associated with high‐dose steroid administration in patients treated with ICIs, and steroid use has been associated with impaired humoral response to SARS‐CoV‐2 mRNA vaccines in patients with cancer. 5 , 19 , 20 However, the effect of different types of anticancer therapy and the concomitant use of steroids on antibody responses to SARS‐CoV‐2 vaccines in patients with UC and RCC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic chemotherapy and ICIs are two immunoregulation agents frequently administered to patients with advanced UC 7–12 . Treatment with ICIs in combination or ICIs plus TKIs is considered the standard of care for patients with metastatic RCC 13–18 . Furthermore, immune‐related AEs are closely associated with high‐dose steroid administration in patients treated with ICIs, and steroid use has been associated with impaired humoral response to SARS‐CoV‐2 mRNA vaccines in patients with cancer 5,19,20 .…”
Section: Introductionmentioning
confidence: 99%